A model for teaching ICT in primary and special education - Dagienė, Valentina; Jasutienė, Eglė; Jevsikova, Tatjana; Zajančkauskienė, Lina; Žilinskienė, Inga (Lietuvos matematikos rinkinys, 2007)
Lithuanian educational strategic provision states that the present poses completely new social, pedagogic and subject requirements for teachers; they must have good information and communication skills. Therefore, we should help teachers, provide relevant materials for education, and allow them to learn the newest things, use innovative methods. One of the ways to achieve that is to provide distant learning for teachers. The paper deals with problems of development of distant course for primary and special needs education teachers. Distant course model (goals, content, and implementation criteria) is presented. Methods of comparative analysis and synthesis of present scientific works are applied.